Suggested guidelines for elementary school teachers to minimize sex stereotyping - Chandra, Barbara Laur; Baldo, Trinidad C. (Quezon City College of Education, University of the Philippines Diliman, 1977)
This paper aimed to raise the consciousness level of teachers to the awareness of sex discrimination which exists in both the Filipino and Western cultures and to eradicate this discrimination by minimizing sex stereotyping of children. This was written to equip teachers with a set of guidelines and examples that will aid them in minimizing sex stereotyping in the classroom setting. These guidelines and their examples were classified into a behavioral and linguistic framework which are divided into the areas of choice of textbooks, choice of instructional materials and the classroom atmosphere. It was found that in order to minimize sex stereotyping, both teachers and school administrators should be educated with these guidelines against sex stereo typing.
Thesis (Master of Arts in Teaching Special Education - Giftedness)--University of the Philippines, Diliman
Keywords: Sex discrimination in education -- Philippines; Elementary school teachers -- Philippines; Special education teachers -- Philippines; Sexism in textbooks